PENANGGULANGAN TINDAK PIDANA PENCUCIAN UANG DI DALAM KERAHASIAAN BANK - Rr Ani Wijayati (Fakultas Hukum Universitas Kristen Indonesia, 2015)
Bank Secrecy (or Financial Privacy) are rights that must be protected from interference by the State and other parties. Bank Secrecy is the soul of a bangking system which is based on the norms of banking practices, contract-based agreement between the bank and its clients, and the written rules set by the State. However, bank secrecy may become one of the factors that trigger the occurrence of money laundering. The factors behind the occurence of money laundering are closely associated with the power or the legislation, and the banking system of a particular country. In other words, the rampant practice of money laundering in a country is closely related to the political will of its government in combating money laundering through its laws and regulations, especially those in the field of banking.